Medios: Elementos para el estudio de la formación de los usos sociales - Gilles Pronovost (Estudios sobre las Culturas Contemporáneas)
The author presents some elements of the uses of the media in two dimensions, theoretical and empirical; elements that relate to eveiyday cultural practices and to the levels of the NTIC (television, videocassettes, and micro-computers) in considering the relations of domination between cultural industries and, intergeneradonally, of individuals in a moment of their lives. Such consumption and control of the use of the media are shaped by a personal and sociological trajectory of practices that are susceptible to modification as well as transformation.